Prevalence of elevated hemoglobin and hematocrit levels in patients with obstructive sleep apnea and the impact of treatment with continuous positive airway pressure: a meta-analysis. Issue 1 (31st December 2022) - Martelli, Vanessa; Carelli, Eric; Tomlinson, George A.; Orchanian-Cheff, Ani; Kuo, Kevin H. M.; Lyons, Owen D.; Ryan, Clodagh M.
ABSTRACT: Objectives: Obstructive sleep apnea (OSA) is reported to be a cause of secondary polycythemia. The present study (i) reviewed the literature reporting the prevalence of secondary polycythemia in patients with OSA and (ii) determined the effect of continuous positive airway pressure (CPAP) therapy on hemoglobin and hematocrit levels in patients with OSA. Methods: We searched MEDLINE, Embase and Cochrane for studies of adult patients with OSA that reported hemoglobin and/or hematocrit levels. We performed summary estimates of (i) polycythemia prevalence and a subgroup analysis according to OSA severity, and (ii) change in hemoglobin and hematocrit levels following treatment with CPAP. Results: Synthesis of seven studies including 3, 654 patients revealed an overall polycythemia prevalence of 2% (95% CI 1–4%); 2% (95% CI 1–3%) in mild-to moderate and 6 % (95% CI 3–12%) in severe OSA. In the pooled analysis of ten single-arm trials including 434 patients, CPAP treatment reduced hemoglobin by 3.76 g/L (95% CI −4.73 to −2.80 g/L). Similarly, pooled analysis of ten single-arm trials including 356 patients without baseline polycythemia showed that CPAP treatment reduced hematocrit by 1.1% (95% CI −1.4 to −0.9%). Conclusion: Our pooled analysis supports an increased prevalence of secondary polycythemia in OSA. This estimated prevalence is likely underestimated due to the change in the polycythemia diagnostic criteria in 2016. Future randomized controlled trials are needed to evaluate the effect of CPAP in patients with baseline polycythemia. HIGHLIGHTS: Pooled analysis shows OSA is associated with an increased prevalence of secondary polycythemia Prevalence of polycythemia is greater in severe OSA CPAP treatment for OSA reduces both the hemoglobin and hematocrit